Modal Analysis for Assessing the Durability of an Automobile Coil Spring Under Random Load - Manouchehry Nya, R.; Abdullah, S.; S.K. Singh, S. (International Journal of Engineering and Technology, 2018)
The aim of this paper is to analyse modal analysis for assessing the durability of an automobile coil spring under random load. Coil spring is subjected to unpredictable loads and random loads; therefore, fatigue life assessment was investigated as a problem in ground vehicle suspension systems. It is important to design coil springs as vital part of ground motor vehicles. In this study, steel SAE 5160 alloy selected as material properties. Finite element analysis was carried out to determine maximum stress/strain von Mises by using linear static approach.Â The original strain-time history signal captured from coil spring of a car during service load. A power spectral density function obtained to analyse modal participations using specific software based on strain history signal. The Coffin-Manson strain life model performed to analyse fatigue life and damage. The results show that maximum fatigue life take-place about Â Â Â cycles based on critical plane strain at critical point.Â Â